2007
DOI: 10.1176/ps.2007.58.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of Aggressive Acts Committed by Chronically Assaultive State Hospital Patients

Abstract: These findings indicate that assaultive behavior among state hospital inpatients is complex and heterogeneous. Because each type of assault requires a different management approach, characterizing aggressive behavior may be important in determining which institutional programs and treatment-plan interventions to implement when addressing inpatient aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 46 publications
3
62
0
4
Order By: Relevance
“…() found that staff–patient interactions were the most frequent antecedents to violent incidents in psychiatric inpatient settings. Staff's communication strategies in tense situations, for instance regarding limit‐setting, were often found to be ineffective in preventing conflicts from escalating (Bowers et al., ; Quanbeck et al., ). Step 2 in SESPI assesses descriptions of patients' affects in specific situations.…”
Section: Discussionmentioning
confidence: 99%
“…() found that staff–patient interactions were the most frequent antecedents to violent incidents in psychiatric inpatient settings. Staff's communication strategies in tense situations, for instance regarding limit‐setting, were often found to be ineffective in preventing conflicts from escalating (Bowers et al., ; Quanbeck et al., ). Step 2 in SESPI assesses descriptions of patients' affects in specific situations.…”
Section: Discussionmentioning
confidence: 99%
“…Bowers et al () also mentioned that interactions between patients and staff who have some decision‐making power tend to be tense and may result in aggressive action. Further, Quanbeck et al () reported that staff were most often the targets of impulsive aggression when they tried to change a patient's unwanted behaviour or refused a patient request. These perspectives might be associated with our finding that ‘staff requiring patient to take medication’ was a common provocation of ‘verbal aggression’ in AP wards.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of chronically aggressive patients, over half were under forensic commitment (Quanbeck et al . ). This result is especially important for the Finnish health‐care systems, where the state mental hospitals' main tasks are to conduct forensic mental examinations and treat criminal patients, but the most violent patients are the civil patients.…”
Section: Discussionmentioning
confidence: 97%
“…Quanbeck et al . () report on data from the United States, where half of the chronically aggressive patients (three or more assaults) were under forensic commitment. One problem in drawing conclusions between these studies is that the results are not proportioned in terms of patient days.…”
Section: Introductionmentioning
confidence: 99%